A high-efficiency and low-temperature subcritical water dechlorination strategy of polyvinyl chloride using coal fly ash (CFA) and coal gangue (CG) as enhancers. (1st July 2020) - Xiu, Fu-Rong; Yu, Xuan; Qi, Yingying
Abstract: In this study, a high-efficiency and low-temperature subcritical water (SubCW) method was proposed for the polyvinyl chloride (PVC) dechlorination using coal fly ash (CFA) and coal gangue (CG) as enhancers. The aim of this work is to evaluate the removal efficiency of chlorine from the PVC waste in the SubCW-CFA/CG process and study the enhancement mechanism of CFA/CG on the dechlorination of PVC. The effective dechlorination temperature can be reduced to 220 °C by using the SubCW-CFA/CG process. The dechlorination efficiency of SubCW-CFA/CG was much higher than that of the reported methods at 200 °C and 220 °C. The optimal processing conditions of SubCW-CFA/CG were as follows: temperature of 220 °C, residence time of 60 min, CFA/CG additive amount of 0.4 g, and solid-to-liquid ratio of 1:30 g/mL. Under the optimal parameters, the chlorine removal efficiency of PVC reached 96% and 97.34% in the SubCW-CFA and SubCW-CG process, respectively. FT-IR and elemental analysis were used to analyze the dechlorination mechanism of PVC. The dechlorination mechanism contains two pathways in the SubCW-CFA/CG process: direct dehydrochlorination and hydroxyl substitution. The direct dehydrochlorination resulted in the generation of polyene structure, and the hydroxyl substitution of C–Cl induced the formation of the stable structure of CO in the SubCW-CFA/CG treatment of PVC. The proposed SubCW-CFA/CG process is believed to be an efficient strategy for the PVC dechlorination at the temperature below 220 °C. Graphical abstract: Image 1 Highlights: A low-temperature (<250 °C) subcritical water process for dechlorination of PVC. Coal fly ash and coal gangue were high-efficiency enhancers for PVC dechlorination. Dechlorination efficiency reached 96% and 97.34% at 220 °C after adding enhancers. Dechlorination mechanism was direct dehydrochlorination and hydroxyl substitution.